Risk of major adverse cardiovascular events in subjects with asymptomatic mild carotid artery stenosis - Kwon, Hyunwook; Kim, Hong-Kyu; Kwon, Sun U.; Lee, Seung-Whan; Kim, Min-Ju; Park, Jee Won; Noh, Minsu; Han, Youngjin; Kwon, Tae-Won; Cho, Yong-Pil (Scientific reports, 2018)
This study aimed to test the hypothesis that the risk of major adverse cardiovascular events (MACE) is similar for subjects with asymptomatic mild and moderate carotid artery stenosis (CAS). We enrolled a total of 453 subjects with asymptomatic CAS (30–69%) detected on baseline screening Doppler ultrasound (DUS) examination between January 2008 and December 2010. The follow-up DUS findings and MACE occurrence (fatal or nonfatal myocardial infarction or stroke and all-cause mortality) were compared between subjects with mild (30–49%) and moderate (50–69%) CAS during the 8-year follow-up period. There was no significant difference in the occurrence of MACE between subjects with mild (n = 289) and moderate (n = 164) CAS (13.8% vs. 15.9%, respectively; p = 0.56), although there was a nonsignificant trend toward an increased risk of major ipsilateral stroke in subjects with moderate CAS (1.4% vs. 4.3%; p = 0.06). Multivariate regression analysis indicated that worsening CAS was independently associated with MACE occurrence (hazard ratio [HR], 4.40; 95% confidence interval [CI], 2.65–7.27; p < 0.01), whereas an increased serum high-density lipoprotein cholesterol level was correlated with a decreased risk of MACE (HR, 0.42; 95% CI, 0.23–0.75; p < 0.01). The cumulative risk of MACE in subjects with asymptomatic mild CAS is similar to that in subjects with asymptomatic moderate CAS.